Pola Hubungan Masyarakat Lintas Agama dalam Mewujudkan Harmonisasi Kehidupan Umat Beragama di Desa Sindang Sari Kecamatan Tanjung Bintang Kabupaten Lampung Selatan - Ruslan, Idrus (AL-ADYAN, 2017)
The pattern of public relations is a social process, which refers to a pattern of dynamic social relations. Sindang Sari Village is one of the villages in Tanjung Bintang District, South Lampung Regency, which has Islamic, Christian, Catholic and Buddhist religious communities, while the people are Javanese, Sundanese, Palembang and Batak. However, the life and association of the religious community is harmonious and there has never been a conflict or dispute with religious and cultural backgrounds. The results of this study indicate how the pattern of community relations in Sindang Sari village is associative, namely the form of relationships that lead to cooperation in various forms of social life, community, and inter-religious relations, all of which are related, or without coercion from any party. While the factors that support the good interfaith relationship are the existence of community habits and awareness to carry the burden borne by other members or citizens by arranging night patrols, mutual cooperation, social gathering or squatting. In addition, the supporters of the relationship between religious communities in the village of Sindang Sari are the existence of support from religious leaders and village officials both formally and informally.